Economic considerations for smallholder cattle milk and meat production and marketing. I. Economic policies, supporting institutions, marketing and demand - Brokken, R.F.; Williams, Timothy O. (International Livestock Centre for Africa, 1990)
Discusses the considerations relating to economic policy, supporting institutions and marketing and consumer demand. Classifies and discusses market functions and analyses market organization and institutions of marketing. Looks into the purpose of marketing studies. Discusses some lessons from past livestock marketing studies.